Analysis of Sports Injury Management in SSB Bintang Muda Sarimulya Athletesitle (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the management of sports injuries management experienced by athletes of SSB Bintang Muda Sarimulya in Tebo Regency. Several athletes often experience minor injuries during training or matches. However, the treatment provided is still quite simple, such as giving only light massages, applying cold compresses without standard procedures, or letting the athletes rest without further medical follow-up. This condition forms the background of this research. The research method used is a descriptive qualitative approach with data collected through in-depth interviews with eight athletes aged 13–17 years, observation, and documentation. The data were analyzed using NVivo 12 software with a thematic analysis approach to identify patterns and relationships between variables. The results show that the most common types of injuries experienced by athletes are ankle injuries (87.5%), abrasions (62.5%), bruises (75%), sprains, and strains. The main causes of injuries include improper footing, physical contact between players, and inadequate field conditions. Preventive efforts carried out include warming up before training, muscle stretching, maintaining physical condition, avoiding risky collisions during play, and cooling down after matches or training. Injury management by athletes generally already follows the RICE method (Rest, Ice, Compression, Elevation) quite well, but there are still limitations in terms of supporting facilities and the availability of professional medical teams within the SSB environment. These findings indicate that although injury management has been carried out properly, adequate facilities and medical personnel are still needed to support the safety and performance of young athletes optimally.